ON THE COMB-TAILED Neohahnia ernsti (SIMON, 1898) (ARANEAE: HAHNIIDAE): REDESCRIPTION AND NEW DISTRIBUTION RECORDS (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Neohahnia ernsti (Simon, 1898) is redescribed and illustrated based on newly examined material. For the first time, the male palp (retrolateral view) and female epigynum (ventral view) are documented. Scanning electron micrographs complement the species' description, and new distribution records are provided. Neohahnia chalupas Dupérré & Tapia, 2024 syn. nov. with N. ernsti (Simon, 1898) is proposed. Previously recorded only in its type locality, N. ernsti is now reported from several Neotropical regions, including location across the Caribbean, such as Saint Vincent Island, Puerto Rico, and Cuba, as well as Venezuela, Colombia, Ecuador, and Brazil. This study expands the known distribution of N. ernsti and offers morphological description into the species. Most specimens were collected from Neotropical rainforests, indicating a possible soil-dwelling habitat.
Keywords: dwarf sheet spiders; Hahniinae; taxonomy